A survey of diversity and inclusiveness initiatives at Carnegie Doctoral Research Institutions libraries. Issue 1 (14th January 2019) - Koury, Regina; Semenza, Jenny Lynne; Shropshire, Sandra
Abstract : Purpose: The purpose of this paper is to describe survey findings on diversity and inclusion initiatives at the Carnegie Doctoral Research Institutions of Higher Education libraries. The findings would be helpful to libraries that are at the beginning of their own diversity and inclusion initiatives or that wish to compare ongoing efforts. Design/methodology/approach: The authors conducted a survey of Carnegie Doctoral Research Institutions of Higher Education libraries using Qualtrics, an online survey software. Link to the survey with a short explanation was e-mailed to the 324 identified contacts and 151 responses were received at the end of the survey. Findings: Survey responses revealed that the most prevalent types of diversity and inclusion initiatives fall into one of three categories. These are the creation/enhancement of library collections, recruitment and collaboration with other campus units. Not surprisingly, lack of money and other resources are identified as challenges faced by those who engage in these initiatives. Originality/value: No other research currently exists for those interested in assessing diversity and inclusion initiatives at the Carnegie Doctoral Research Institutions of Higher Education libraries.